2021
DOI: 10.1101/2021.06.24.449704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell atlas of de novo β-cell regeneration reveals the contribution of hybrid β/δ-cells to diabetes recovery in zebrafish

Abstract: Regeneration-competent species possess the ability to reverse the progression of severe diseases by restoring the function of the damaged tissue. However, the cellular dynamics underlying this capability remain unexplored. Here, we use single-cell transcriptomics to map the cellular dynamics underlying de novo β-cell regeneration during induction and recovery from diabetes in zebrafish. We show that the zebrafish has evolved two distinct types of somatostatin-producing δ-cells, which we term δ1- and δ2-cells. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
(79 reference statements)
2
2
0
Order By: Relevance
“…Their capacity to regulate blood glucose levels is corroborated by their transcriptomic profile showing the expression of the machinery required for glucose responsiveness and insulin secretion as illustrated by the glucose transporter Glut2 (slc2a2), the prohormone convertase pcsk1, the K ATP subunit SUR1 (abcc8) and several components of the secretory pathway. All these findings are further supported by the observation by Singh et al that β/δ hybrid cells gain glucose responsiveness during regeneration as assessed by in vivo Calcium imaging (Singh et al, 2021). Altogether, we propose that, despite the fact that bihormonal cells are not identical to β-cells, they are the functional units that control glucose homeostasis in regenerated fish, compensate for the absence of monohormonal β-cells and reverse diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their capacity to regulate blood glucose levels is corroborated by their transcriptomic profile showing the expression of the machinery required for glucose responsiveness and insulin secretion as illustrated by the glucose transporter Glut2 (slc2a2), the prohormone convertase pcsk1, the K ATP subunit SUR1 (abcc8) and several components of the secretory pathway. All these findings are further supported by the observation by Singh et al that β/δ hybrid cells gain glucose responsiveness during regeneration as assessed by in vivo Calcium imaging (Singh et al, 2021). Altogether, we propose that, despite the fact that bihormonal cells are not identical to β-cells, they are the functional units that control glucose homeostasis in regenerated fish, compensate for the absence of monohormonal β-cells and reverse diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…All these observations support the conclusion that sst1.1 -cells constitute a distinct zebrafish -cell population expressing -cell features enabling them to rapidly reprogram to bihormonal cells by activating ins expression and engender functional surrogate-cells. Importantly, during the preparation of our manuscript, Singh et al also identified sst1.1+ ins+ δ/β hybrid cells in zebrafish by scRNAseq (Singh et al, 2021). They also proposed the sst1.1 -cells as possible cellular origin after β-cell ablation, thereby consolidating our findings.…”
Section: Discussionsupporting
confidence: 72%
“…These analyses reveal how microbiota stimulate both tissue growth and function, promoting developmental plasticity in response to the microbial environment. The transcriptional plasticity of pancreatic cells has also been demonstrated at single cell resolution within regenerating islets of the zebrafish endocrine pancreas (Singh et al ., 2022). In the artificial GF state, the exocrine pancreas appears to be stunted and composed of fully differentiated acinar cells that, based on their transcriptional patterns, are poised in a functionally inactive state, a situation that may require upregulation of cytoprotective Cry proteins to maintain.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous zebra sh studies have focused on the phase of functional recovery, which we identi ed in this study. They reported that α cells, δ1 cells, β/δ1 hybrid cells, and some endocrine progenitor cells contribute to β cell regeneration 5,[8][9][10]16 . Our current results suggest that these cells already express Neurod1 or express Neurod1 within 24 hours after β cell ablation and that Neurod1 expression is a common characteristic of cells which give rise to the regeneration of β cells.…”
Section: Discussionmentioning
confidence: 99%